ACÚMULO DE MACRONUTRIENTES EM GRÃOS DE TRIGO E OS EFEITOS PROPORCINONADOS PELA EPÓCA DE DOSES DE NITROGÊNIO - Becker, Raquel W.; Bosa, Diogo; Cadore, Pablo R.; Dambrós, Rodrigo; Silveira, Rafaela B. d.; Soares, Rômulo D.; Melo, Elder D.; Persich, Daiana L.; Carbonera, Roberto; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo